IDENTIFIKASI PERKIRAAN BATUAN ASAL SEDIMEN LEMPUNG PADA PERMUKAAN DASAR LAUT PERAIRAN INDRAMAYU BERDASARKAN PENDEKATAN ANALISIS GEOKIMIA DAN INDEKS PROPERTIS - Kris Budiono (Jurnal Geologi dan Sumberdaya Mineral, 2008)
The bottom sea surface sediments of Indramayu water is characterized by differences of type and distribution of these sediments.The geochemistry and index properties tests give the information about the natural condition of water content and the other physics and chemical properties of sediments. The empirical relation have been developed between index properties and general properties for land soil or sediments. Most of that empirical relationship can be applied for marine surficial sediments, because in general the terrigenous sediments that similar Â with the sediments which was transported from land or coastal zone to the bottom sea. The result of geochemistry and index properties test shows that the characteristics of sediments in Indramayu sea water appear to be difference from one sample to the another sample. This condition is probably caused by the difference of distribution of clay minerals or the rock origin of sediments .Key word : Geochemistry and Index properties, clay sediments, sea bottom surface sediments.